2007
DOI: 10.1063/1.2644459
|View full text |Cite
|
Sign up to set email alerts
|

New Regularization Method for EXAFS Analysis

Abstract: As an alternative to the analysis of EXAFS spectra by conventional shell fitting, the Tikhonov regularization method has been proposed [1]. An improved algorithm that utilizes a priori information about the sample has been developed and applied to the analysis of U L 3-edge spectra of soddyite, (UO 2) 2 SiO 4 •2H 2 O, and of U(VI) sorbed onto kaolinite. The partial radial distribution functions g 1 (UU), g 2 (USi), and g 3 (UO) of soddyite agree with crystallographic values and previous EXAFS results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…On this basis, it can be concluded that U(VI) forms two surface species on kaolinite that differ in the amount of water molecules in their coordination environment. Furthermore, from EXAFS measurements of U(VI) sorption onto kaolinite (33) it was concluded that U(VI) forms inner-sphere surface complexes. Moreover, two U-Si/Al interactions were found by EXAFS, which means that these surface complexes are bidentate.…”
Section: Disscusionmentioning
confidence: 99%
“…On this basis, it can be concluded that U(VI) forms two surface species on kaolinite that differ in the amount of water molecules in their coordination environment. Furthermore, from EXAFS measurements of U(VI) sorption onto kaolinite (33) it was concluded that U(VI) forms inner-sphere surface complexes. Moreover, two U-Si/Al interactions were found by EXAFS, which means that these surface complexes are bidentate.…”
Section: Disscusionmentioning
confidence: 99%
“…On the other hand, sawteeth are also known to react back on the fast ion population during the sawtooth collapse. Measurements done just before and just after a sawtooth collapse indicate that in some conditions the sawtooth collapse itself is associated with a reduction of the central fast ion population of up to 50% [14][15][16][17][18]. The sawtooth collapse is also believed to reduce the fast ion density in certain parts of phase space.…”
Section: Introductionmentioning
confidence: 99%
“…RDFs reveal the relative positions of different pairs of atoms in a sample, avoiding the a priori reference to a structural model. Results for uranyl adsorption on kaolinite, obtained by conventional fitting [30][31][32][33][34], have independently been confirmed [40] with this approach; yet, it does not resolve the problem of differentiating Al and Si centers.…”
Section: Resultsmentioning
confidence: 54%
“…Recently an alternative regularization method for the analysis of EXAFS results was suggested [40]. Instead of trying to find the best structural model that fits the data, radial distribution functions (RDFs) have been determined directly from EXAFS data [40]. RDFs reveal the relative positions of different pairs of atoms in a sample, avoiding the a priori reference to a structural model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation